Fuzzy Adaptive Control for Multi-Dimensional Temperature Regulation in Electrical Equipment: A Comparative Analysis with PID Control - Wang, Miao; Zhu, Qinghua (Informatica, 2026)
This study proposes a fuzzy adaptive control system for multi-dimensional temperature regulation in electrical equipment and compares its performance against a traditional PID control system. Experiments were conducted under controlled ambient temperatures (15–45°C) and load conditions (0.5–5 kW), evaluating temperature stability (±0.5°C setpoint), response time, and energy efficiency. Results demonstrate that the fuzzy adaptive system reduced temperature fluctuations by 32.7% and improved energy efficiency by 18.4% compared to PID control. The fuzzy controller-maintained temperature within ±0.8°C under dynamic disturbances, outperforming PID (±2.5°C). These findings highlight the superiority of fuzzy adaptive control in complex thermal environments, offering enhanced stability and energy savings for industrial applications.